Clinical characteristics and antithrombotic status in 621 very elderly hospitalized patients with atrial fibrillation - Wen Liu; Zhi-Feng Qiu; Li Wang; Yan-Fang Zhang; Jia-Nan Chen; Lei Wu; Jun-Zhou Xin (Cardiology Plus, 2018)
Background: The prevalence of atrial fibrillation (AF) increases with age and is associated with high morbidity and mortality. The main objective of this study is to describe the clinical characteristics and antithrombotic status and the factors that determine antithrombotic use in hospitalized elderly patients with AF. Methods: Data were collected involving patients hospitalized at the First Affiliated Hospital of Shihezi Medical University from June 2015 to September 2017. Results: A total of 621 patients with an average age of 82.4 ± 5.0 years (42.3% females; 91.8% Han) were included. The prevalence of risk factors and cardiovascular disease: hypertension (56.5%), heart failure (38.2%), coronary artery disease (76.8%), and carotid atherosclerosis (21.3%). Among the 621 patients, 35.7% were taking oral anticoagulant therapy (OAT) including warfarin (25.6%) or a novel oral anticoagulant (10.1%), 32.4% of patients were taking oral antiplatelet therapy, and 31.9% received 17 anticoagulant therapy. According to the European Guidelines for AF management, CHA2DS2-VASc score was used for stroke risk stratification. All patients in this study had a score of ≥2; However, the rate of OAT was 35.7%. Follow-up data were available for 97.3% of the patients (n = 604), of which 26.6% of patients (n = 159) were deceased and 16.75% of patients (n = 104) continued to receive anticoagulation treatment. Hospitalized patients older than 80 years with AF showed numerous comorbidities. The percentage of appropriately anticoagulated patients was suboptimal according to CHA2DS2-VASc score, with only 35.7% of those requiring treatment receiving it. Conclusion: The percentage of patients with AF appropriately anticoagulated at the First Affiliated Hospital of Shihezi Medical University is at a substandard level.